Capital investment decision making under uncertainty: perspectives of an emerging economy / Lingesiya Kengatharan. - Kengatharan, Lingesiya (Accounting Research Institute and UiTM Press, Universiti Teknologi MARA, 2017)
This study examines the capital investment decision making under uncertainty since the application of investment appraisal practices trends towards increasing greater superiority with the performing of multiple tools and procedures in the current investment markets which are evolving within an increasingly volatile and intertwined with global network, investments are strongly exposed to uncertainties. Therefore, this study focused on investment decision making under uncertainty of emerging market economy of 186 Sri Lankan companies. A comprehensive primary survey was conducted to collect data and exploratory factor analysis had been performed to identify the uncertainty factors. The hierarchical multiple regression analysis was performed to investigate the impact of uncertainty on the application of capital budgeting practices in investment decision making. The results of the study revealed that an increase in financial uncertainty was associated with the application of net present value (NPV) based advanced capital budgeting and sophisticated capital budgeting practices and the size of the company was also related to the application of NPV based and sophisticated capital budgeting practices.